2022
DOI: 10.1111/1365-2664.14293
|View full text |Cite
|
Sign up to set email alerts
|

Native bacteria and cyanobacteria can influence seedling emergence and growth of native plants used in dryland restoration

Abstract: 1. Seed-based ecosystem restoration has huge potential to restore degraded drylands. However, fewer than 10% of directly sown seeds transition to established seedlings. One of the potential factors restricting plant establishment in degraded soils is the low abundance and diversity of native soil micro-organisms.In this study, we investigated whether returning indigenous bacteria and cyanobacteria consortia to degraded dryland soils improved seedling emergence, survival and growth of native plants.2. We inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…However, none of these studies test the effects of these strains in extruded pellets as employed here. Despite a paucity of comparable studies on the effectiveness of microbial amendments, commercially available or otherwise, in similar encapsulations (Brown et al 2021), there is increasing evidence in this area (Dadzie et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of these studies test the effects of these strains in extruded pellets as employed here. Despite a paucity of comparable studies on the effectiveness of microbial amendments, commercially available or otherwise, in similar encapsulations (Brown et al 2021), there is increasing evidence in this area (Dadzie et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that any emergence and seedling growth benefits from plant‐growth‐promoting bacteria in the amended pellets may also have been diminished due to there being very few limiting‐factors to plant growth including accessible nutrients and the relevant native microbes likely already present in the potting tube soil and compost‐based pellet mixtures. There is growing evidence that extruded pellets designed to deliver beneficial native microbes (Roman et al 2020; Dadzie et al 2022) or otherwise promote favorable microbiomes (Stock et al 2020) may prove to be beneficial in highly degraded lands (such as post‐mining soils and tailings) where nutrient profiles and native microbial communities are often damaged and seedling establishment and growth are below target levels (Muñoz‐Rojas et al 2016; Wu et al 2019; Koziol et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Currently large parts of dry forests are threatened by desertification caused by unsustainable anthropogenic land exploitation ( Miles et al, 2006 ; Vieira et al, 2015 ). However, biocrusts have been proven to be useful tools for nature-based dryland restoration and to combat land degradation and desertification ( Dadzie et al, 2022 ; Maggioli et al, 2022 ). Their influence could become even more important, since dry forests will face dramatic changes and climate extremes, particularly an increase in drought stress for vascular plants ( Torres et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The plant species specific differences in response to microbial inoculums seen here are consistent with what has been reported previously. For example, Dadzie et al [ 68 ] found that the benefit of cyanobacteria or native heterotrophic bacteria on plant establishment from extruded pellets was species specific and the former inoculation resulted in a 11% reduction in growth of Triodia epactia (Poaceae) seedlings. Similarly, the application of commercially-available soil microbial amendments in semi-arid ecosystems has been shown have varying effects on plant fitness, possibly as a result of plant-microbiome physiological mismatching as well as issues of low persistence of consortium members [ 25 ].…”
Section: Discussionmentioning
confidence: 99%